Clinical experience with biologic agents in hospital Selayang, Malaysia - Woon Pang, Kuan; Abdullah, Hilmi; Mohamad Ismail, Asmahan; Rosman, Azmillah (Wiley-Blackwell Publishing Asia, 2010)
: The efficacy of biologic agents had been shown by many clinical trials and it had been widely used in developed countries in treating various rheumatologic diseases. But it is not universally effective in all patients and it comes with a relatively high economic burden. The experiences with biologic agents are quite limited in developing countries such as Malaysia